On the synthesis of 3-cyano-6-hydroxy-4-methyl-2-pyridone at room temperature - Miodrag V. Zdujić; Dušan Ž. Mijin (Zaštita Materijala)
Milling of cyanoacetamide and acetoacetic ester as reactants, in the presence of KOH as the catalyst and ethanol as a viscous control agent (VCA) was performed in a planetary ball mill with the goal of investigating the effect of mechanochemical treatment for the synthesis of 3-cyano-6hydroxy-4-methyl-2-pyridone at room temperature. The mechanochemical synthesis was performed under various milling parameters, i.e. milling time up to 4 h, number and size of balls, angular velocity as well as molar ratio of reactants and the amount of catalyst. The obtained product was characterized by m.p., UV, IR and NMR data. It was fond that the dominant process parameter is the milling time while others are of less importance. The highest isolated yield after milling was up to 56%. The combination of milling and aging increase yield over 60%.